Sugarcane trash: a valuable dry fodder source for dairy animals - Rao, S B N; Gowda, N K S; Soren, N; Prasad, K S (Indian Farming, 2018)
Sugarcane trash is only substitute to dry fodder like wheat or rice straw. It needs to chaffed mechanically under intensive dairy farmingsituations. The chaffed Sugarcane trash needs to be mixed with green fodder and concentrate as a total mixed ration for maximizing intake.